Friction material

JP7651475B2Active Publication Date: 2025-03-26AKEBONO BRAKE IND CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021565575
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-19
Filing Date
2020-12-14
Publication Date
2025-03-26
Estimated Expiration
2040-12-14

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、十分な摩擦係数を有し、ブレーキ鳴きを抑制することができる、強度が高い摩擦材を提供することができる。 また、本発明の摩擦材は、相手材攻撃性を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651475000001
    Figure 0007651475000001
Patent Text Reader

Abstract

The problem addressed by the present invention is to provide a friction material having a sufficient friction coefficient, being capable of suppressing brake squeal, and having high strength. The present invention relates to a friction material comprising a friction adjusting material, a binder, and a fiber base material, the friction material containing steel fibers as the fiber base material, natural graphite as a lubricant, and no titanate, wherein the content of copper is 0.5% by mass or less in terms of copper element.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a friction material for use in automobiles, railway vehicles, industrial machines, and the like. [Background technology]

[0002] When braking, the vibrations generated by the contact between the friction material and the mating material can be amplified by the mating material itself, resulting in an unpleasant noise. This unpleasant noise is called brake squeal, and car users would like to suppress brake squeal as much as possible.

[0003] As an example of a friction material capable of suppressing brake squeal, Patent Document 1 discloses a non-asbestos-based friction material obtained by molding and curing a non-asbestos-based friction material composition mainly composed of a fiber base material containing at least steel fibers, excluding asbestos, a binder, and a filler, and characterized in that the non-asbestos-based friction material contains petroleum coke having an average particle size of 50 to 150 μm and hard inorganic particles having an average particle size of 5 to 30 μm.

[0004] Furthermore, since friction materials are required to have sufficient strength, titanates are sometimes contained in the friction materials in order to improve the strength.

[0005] As an example of a friction material having improved strength by using a titanate, Patent Document 2 discloses a friction material that does not contain a simple metal or an alloy, characterized in that the friction material contains a plate-like titanate having an average particle size of 10 to 50 μm and hydrous magnesium silicate in a total amount of 20 to 30 volume % based on the total amount of the friction material, and the volume ratio of the titanate to the hydrous magnesium silicate is 12:1 to 5:1. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 2004-155843 [Patent Document 2] Japanese Patent Publication No. 2012-197352 Summary of the Invention [Problem to be solved by the invention]

[0007] However, according to the investigations of the present inventors, although the friction material described in Patent Document 1 can suppress brake squeal, it does not have a sufficient friction coefficient. Furthermore, in the friction material described in Patent Document 2, the titanate may form a transfer film on the surface of the mating material, resulting in a decrease in the coefficient of friction.

[0008] The present invention has been made in consideration of the above-mentioned conventional situation, and has as its object to provide a friction material having a sufficient friction coefficient, capable of suppressing brake squeal, and high strength. [Means for solving the problem]

[0009] As a result of extensive research, the inventors have discovered that by incorporating steel fibers as a fiber base material and natural graphite as a lubricant in a friction material, the strength of the friction material can be improved without incorporating titanate, and further, a sufficient friction coefficient can be imparted and brake squeal can be suppressed, thereby completing the present invention.

[0010] That is, the present invention provides the following <1> ~ <5> This is regarding. <1> A friction material comprising a friction modifier, a binder and a fibrous base material, The fiber base material contains steel fibers, Contains natural graphite as a lubricant. The copper content is 0.5% by mass or less in terms of elemental copper, A friction material that does not contain titanates. <2> The content of the natural graphite is 1.0 to 5.0 mass%. <1> The friction material according to claim 1. <3> The content of the steel fibers is 10 to 50 mass%. <1> or <2> The friction material according to claim 1. <4> The lubricant further contains coke. <1> ~ <3> 13. The friction material according to claim 12, <5> Contains magnesium oxide as an abrasive, <1> ~ <4> 13. The friction material according to claim 12, Effect of the Invention

[0011] According to the present invention, it is possible to provide a friction material having a sufficient friction coefficient, capable of suppressing brake squeal, and high strength. Furthermore, the friction material of the present invention can suppress attacking the mating material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below, however, these are examples of preferred embodiments and the present invention is not limited to the contents thereof.

[0013] The friction material of the present invention comprises a friction modifier, a binder and a fibrous base material. Each component will be described in detail below.

[0014] <Friction adjustment material> Examples of the friction modifier include lubricants, abrasives, and other friction modifiers (inorganic fillers, organic fillers).

[0015] (Lubricant) The friction material of the present invention contains natural graphite as a lubricant. Natural graphite is a graphite that occurs naturally as an ore. Since natural graphite has high lubricity, when the friction material of the present invention contains natural graphite, it is possible to suppress the friction material's attack on the mating material and brake squeal.

[0016] Natural graphite can be classified into scaly graphite, flake graphite, and amorphous graphite depending on its appearance. Of these, it is preferable to use scaly graphite, which has the highest lubricity.

[0017] Flaky graphite is natural graphite that exists mostly in the form of veins and has a scaly (lumpy) appearance. Because the particles of flaky graphite are scaly (lumpy), they have a small aspect ratio, and compared to flake graphite and earthy graphite, they have a high degree of crystallinity and are thicker. Therefore, flaky graphite has very high lubricity.

[0018] The content of natural graphite in the entire friction material is preferably 1.0 to 5.0 mass%, more preferably 1.2 to 4.5 mass%, and further preferably 1.5 to 4.0 mass%. If the content of natural graphite is 1.0 mass% or more, sufficient lubrication can be imparted to the friction material of the present invention, so that the friction material's attack on the mating material and brake squeal can be suppressed. If the content of natural graphite is 5.0 mass% or less, a decrease in the friction coefficient due to excessive lubrication of the friction material can be prevented.

[0019] The average particle size of the natural graphite is preferably 1 to 200 μm, more preferably 3 to 100 μm, and further preferably 5 to 100 μm. If the average particle size of the natural graphite is 1 μm or more, the lubricity of the friction material is improved and attacking of the counter material can be suppressed. If the average particle size of the natural graphite is 200 μm or less, a decrease in the friction coefficient during high-speed braking can be prevented.

[0020] In the present invention, the average particle size refers to a value (median diameter) measured by a laser diffraction particle size distribution measuring device. The average particle size can also be measured by a sieving method.

[0021] The friction material of the present invention preferably contains coke as a lubricant. When the friction material of the present invention contains coke, the lubrication effect of the coke can suppress the attack of the friction material on the mating material.

[0022] There are two types of coke: coal coke and petroleum coke, and either can be used.

[0023] The content of coke in the entire friction material is preferably 3.0 to 10.0 mass %, more preferably 4.0 to 9.0 mass %, and further preferably 5.0 to 8.0 mass %, from the viewpoint of suppressing attack on the mating material.

[0024] The average particle size of the coke is preferably 200 to 1000 μm, more preferably 300 to 900 μm, and further preferably 400 to 800 μm. If the average particle size of the coke is 200 μm or more, the lubricity of the friction material is sufficient and the wear resistance can be improved. If the average particle size of the coke is 1000 μm or less, the coke is less likely to fall off the friction material and the deterioration of wear can be suppressed.

[0025] In addition to the above, examples of the lubricant include artificial graphite, antimony trisulfide, molybdenum disulfide, tin sulfide, polytetrafluoroethylene (PTFE), etc. Each of the lubricants may be used alone or in combination of two or more kinds.

[0026] The content of the lubricant in the entire friction material is preferably 1 to 40 mass %, more preferably 3 to 35 mass %, and further preferably 5 to 30 mass %, from the viewpoint of suppressing attack on the mating material and brake squeal.

[0027] (Abrasives) Examples of the abrasive include magnesium oxide, alumina, silica, zirconia, zirconium silicate, chromium oxide, iron oxide trioxide (Fe3O4), chromite, etc. The abrasives may be used alone or in combination of two or more kinds.

[0028] The content of the abrasive in the entire friction material is preferably 3 to 35 mass %, more preferably 5 to 30 mass %, and further preferably 10 to 25 mass %, from the viewpoint of imparting appropriate grinding ability.

[0029] The friction material of the present invention preferably contains magnesium oxide as an abrasive. The Mohs hardness of magnesium oxide is about 6, which is slightly higher than the Mohs hardness of the mating material, cast iron, which is 4. When magnesium oxide is contained in the friction material of the present invention, the sliding surface of the mating material can be appropriately ground compared to the case where only other abrasives are used, and the friction coefficient can be improved.

[0030] The content of magnesium oxide in the entire friction material is preferably 3.0 to 10.0 mass %, more preferably 4.0 to 9.0 mass %, and further preferably 5.0 to 8.0 mass %, from the viewpoint of suppressing an increase in the friction coefficient.

[0031] From the viewpoint of improving the coefficient of friction, the average particle size of magnesium oxide is preferably from 1 to 100 μm, more preferably from 10 to 90 μm, and further preferably from 25 to 80 μm.

[0032] (Other friction modifiers) Other friction modifiers (inorganic and organic fillers) are used to impart desired friction characteristics to the friction material, such as wear resistance, heat resistance, and fade resistance.

[0033] Examples of inorganic fillers include inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica, and metal powders such as aluminum, tin, and zinc. These may be used alone or in combination of two or more.

[0034] Examples of organic fillers include various rubber powders (raw rubber powder, tire powder, etc.), cashew dust, tire tread, melamine dust, etc. These may be used alone or in combination of two or more.

[0035] From the viewpoint of imparting the above-mentioned desired friction characteristics to the friction material sufficiently, the friction modifier is used in an amount of preferably 20 to 80 mass %, and more preferably 30 to 70 mass %, of the entire friction material.

[0036] <Binding material> As the binder, various commonly used binders can be used, specifically, thermosetting resins such as phenolic resin, modified phenolic resin, melamine resin, epoxy resin, polyimide resin, etc.

[0037] Examples of modified phenolic resins include elastomer-modified phenolic resins, etc. Examples of elastomer-modified phenolic resins include acrylic rubber-modified phenolic resins, silicone rubber-modified phenolic resins, nitrile rubber (NBR)-modified phenolic resins, etc. These may be used alone or in combination of two or more.

[0038] From the viewpoint of formability of the friction material, the binder is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire friction material.

[0039] <Fiber base material> The friction material of the present invention contains steel fibers as a fibrous base material. When the friction material of the present invention contains steel fibers, the friction material of the present invention has high strength and can improve the friction coefficient during fading.

[0040] The content of the steel fibers in the entire friction material is preferably 10 to 50 mass %, more preferably 20 to 45 mass %, and further preferably 25 to 40 mass %. If the steel fiber content is 10% by mass or more, the strength of the friction material can be sufficiently ensured, and if the steel fiber content is 50% by mass or less, the friction material can be prevented from becoming too heavy.

[0041] The average fiber length of the steel fibers is preferably 0.5 to 30 mm, more preferably 0.5 to 20 mm, and further preferably 0.5 to 10 mm. If the average fiber length of the steel fibers is 0.5 mm or more, the strength of the friction material can be ensured. If the average fiber length of the steel fibers is 30 mm or less, the deterioration of the attacking property of the counter material can be suppressed.

[0042] The average fiber diameter of the steel fibers is preferably 10 to 600 μm, more preferably 30 to 500 μm, and further preferably 50 to 400 μm. If the average fiber diameter of the steel fibers is 10 μm or more, the strength of the friction material can be ensured. If the average fiber diameter of the steel fibers is 600 μm or less, the deterioration of the attacking property against the counter material can be suppressed.

[0043] In the present invention, the average fiber length and average fiber diameter of the steel fibers can be measured by observation using a microscope or the like.

[0044] In addition to the above, examples of the fibrous substrate include organic fibers, inorganic fibers, etc. Each of the fibrous substrates may be used alone or in combination of two or more kinds.

[0045] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.

[0046] Examples of inorganic fibers include biosoluble inorganic fibers, ceramic fibers, glass fibers, carbon fibers, rock wool, etc. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, and biosoluble rock wool.

[0047] From the viewpoint of ensuring the strength of the friction material, the fibrous base material is used in an amount of preferably 10 to 60 mass %, and more preferably 20 to 60 mass %, of the entire friction material.

[0048] From the viewpoint of reducing the environmental load, the copper content in the entire friction material of the present invention is 0.5 mass % or less in terms of copper element, and it is preferable that the friction material of the present invention does not contain a copper component.

[0049] In addition, the friction material of the present invention does not contain titanate. By not containing titanate, it is possible to prevent the formation of a transfer film on the surface of the mating material by titanate, which would otherwise cause a decrease in the coefficient of friction.

[0050] <Method of manufacturing friction material> The friction material of the present invention can be produced by a known production process, for example, by blending the above-mentioned components and subjecting the blend to steps of preforming, thermoforming, heating, polishing, etc. according to a conventional production method.

[0051] A method for manufacturing a brake pad having a friction material generally includes the following steps. (a) A process of forming a pressure plate into a desired shape using a sheet metal press. (b) A process of degreasing, chemical conversion and primer treatment on the pressure plate, and applying an adhesive. (c) A process of blending raw materials such as friction modifiers, binders, and fiber base materials, thoroughly homogenizing them by mixing, and molding them at room temperature under a predetermined pressure to produce a preform. (d) A thermoforming process in which the preform and the pressure plate coated with adhesive are bonded together by applying a predetermined temperature and pressure (molding temperature: 130 to 180°C, molding pressure: 30 to 80 MPa, molding time: 2 to 10 minutes). (e) After-curing (150-300°C, 1-5 hours) and final finishing such as polishing, scorching, and painting. EXAMPLES

[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.

[0053] (Examples 1 to 14, Comparative Examples 1 to 2) The ingredients shown in Table 1 were all charged into a mixer and mixed at room temperature for 5 minutes to obtain a mixture. The natural graphite used was "CD-150" (manufactured by Nippon Graphite Industries Co., Ltd.). The resulting mixture was subjected to the following steps of preforming (i), thermoforming (ii), heat treatment and scorching (iii) to produce a friction material.

[0054] (i) Preforming The mixture was placed in a mold of a preforming press and molded at room temperature at 20 MPa for 10 seconds to prepare a preforming body. (ii) Thermoforming This preform was placed in a thermoforming mold, and a metal plate (pressure plate) to which an adhesive had been applied was placed on top of it, followed by heat and pressure molding at 150° C. and 50 MPa for 6 minutes. (iii) Heat treatment, scorch This hot-pressed compact was heat-treated at 250° C. for 3 hours, and then the surface was polished. Next, the surface of this hot-pressed molded product was subjected to a scorch treatment and then finished with a coating to obtain a friction material.

[0055] The friction materials obtained in Examples 1 to 14 and Comparative Examples 1 and 2 were evaluated for strength, friction performance, attack on mating materials, and brake squeal by the following methods. The results are shown in Table 1.

[0056] <Strength> The room temperature shear strength of the friction material obtained above was measured in accordance with JIS D4422 (adhesive area: 50 cm 2 The measured value is the shear force per unit area (N / cm2) calculated by dividing the stress at the time of shear failure by the area of ​​the friction material. 2 ) was calculated.

[0057] The measured shear strength was evaluated based on the following criteria. ◎: 600N / cm 2 End ○: 500N / cm 2 More than 600N / cm 2 less than △: 400N / cm 2 More than 500N / cm 2 less than

[0058] <Friction performance> The friction materials obtained above were subjected to a friction performance test in accordance with JASO C406 using a dynamometer to measure the friction coefficient at the second pull (initial speed 130 km / h, deceleration 0.6 G) and the minimum friction coefficient at the first fade.

[0059] The friction coefficient at the measured second force was evaluated based on the following criteria. ◎: 0.40 or more ○: 0.35 or more and less than 0.40 △: 0.30 or more and less than 0.35 ×: Less than 0.30

[0060] The minimum friction coefficient in the first fade measured was evaluated according to the following criteria. ◎: 0.30 or more ○: 0.25 or more and less than 0.30 △: 0.20 or more and less than 0.25 ×: Less than 0.20

[0061] <Aggression against opposing materials> After the friction performance test, the wear amount of the mating material was measured and evaluated based on the following criteria. ◎: 15μm or less ○: More than 15μm and less than 20μm △: More than 20μm but less than 25μm ×: More than 25μm

[0062] <Brake squeal> The friction material obtained above was mounted on an actual vehicle, and a brake squeal test was conducted in accordance with JASO C402 to measure the intensity (dB) of brake squeal. The occurrence rate (%) of brake squeal of 70 dB or more was calculated using the following formula. Occurrence rate of brake squeal of 70 dB or more (%) = {Number of occurrences of brake squeal of 70 dB or more (times) / Number of braking operations (times)} x 100

[0063] The calculated occurrence rate (%) of brake squeal of 70 dB or more was evaluated based on the following criteria. ◎:0% ○: Over 0% and less than 5% △: 5% to less than 10% ×: More than 10%

[0064] [Table 1]

[0065] From the results in Table 1, it was found that the friction materials according to Examples 1 to 14 had high strength, a sufficient friction coefficient, and were capable of suppressing attack on the mating material and brake squeal.

[0066] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-229438) filed on December 19, 2019, the contents of which are incorporated herein by reference.

Claims

1. A friction material comprising a friction modifier, a binder and a fiber base material, The fiber base material contains steel fibers, The lubricant contains 2.0 to 4.0 mass% natural graphite, The copper content is 0.5% by mass or less in terms of elemental copper, A friction material that does not contain titanates.

2. The friction material described in claim 1, containing chromium oxide as the friction modifier.

3. The friction material of claim 1, which does not contain chromite.

4. The friction material according to any one of claims 1 to 3, wherein the content of the steel fibers is 10 to 50 mass %.

5. The friction material according to any one of claims 1 to 4, further comprising coke as the lubricant.

6. 6. The friction material according to claim 1, which contains magnesium oxide as an abrasive.

7. The friction material as described in claim 5, wherein the coke content is 8.0 mass% or less.

8. The friction material as described in claim 6, wherein the magnesium oxide content is 8.0 mass% or less.

Citation Information

Patent Citations

  • Low-metal ceramic-based drum-type brake pad and preparation method thereof

    CN101813149A

  • Multielement resin base carbon compound disc-type braking pad and preparation method thereof

    CN102635653A

  • Calcium carbonate whisker reinforced rubber base friction material and preparation method therefor

    CN105111532A

  • Calcium carbonate whisker reinforced resin-rubber base friction material and preparation method therefor

    CN105111675A

  • Copper- and antimony-free environment-friendly friction material and friction plate, and preparation method and application

    CN109929511A